MOF-like supramolecular network of Mn3 single-molecule magnets formed by extensive π–π stacking. (8th January 2016) - Nguyen, Tu N.; Abboud, Khalil A.; Christou, George
Graphical abstract: The carboxylate substitution reaction of triangular [Mn3 O(O2 CMe)3 (mpko)3 ](ClO4 ) (mpkoH = methyl(2-pyridyl)ketone oxime) with 3, 5-dihydroxybenzoic acid (dhbH) has yielded a MOF-like 3-D network formed by extensive formation of inter-Mn3 π–π stacking interactions. The repeating unit is an [Mn3 ]8 rhombohedron, and the voids in the network each contain eight MeCN molecules. VT magnetic susceptibility studies reveal antiferromagnetic inter-Mn3 exchange couplings. Abstract: [Mn3 O(dhb)3 (mpko)3 ](ClO4 ) (4 ) has been obtained from the carboxylate substitution reaction of triangular [Mn3 O(O2 CMe)3 (mpko)3 ](ClO4 ) (mpkoH = methyl(2-pyridyl)ketone oxime) with 3, 5-dihydroxybenzoic acid (dhbH). Complex4 possesses an equilateral triangle [Mn3 O] 7+ core with the dhb − and mpko − ligands on opposite sides of the Mn3 plane. All dhb − and mpko − groups are involved in π–π stacking interactions with those on neighboring Mn3 molecules to give a 3-D supramolecular network resembling a metal–organic framework (MOF), with periodic voids resulting from a repeating unit comprising an [Mn3 ]8 rhombohedron. Variable-temperature, solid-state magnetic susceptibility studies in the 5.0–300 K temperature range reveal the predominance of antiferromagnetic inter-Mn3 exchange couplings. Alternating current magnetic susceptibility studies on4 show that the single-molecule magnet (SMM) behavior characteristic of [Mn3 O(O2 CR)3 (mpko)3 ] + complexes has been lost. This work demonstrates that constructing MOF-like networks from SMMs by weak interactions is feasible but that even these can introduce significant inter-SMM exchange interactions that weaken or destroy the SMM properties.